2019
DOI: 10.1177/0954406219840385
|View full text |Cite
|
Sign up to set email alerts
|

IZOD impact properties of full-density fused deposition modeling polymer materials with respect to raster angle and print orientation

Abstract: One of the fundamental characteristics of additively processed materials is that they are naturally anisotropic; this variance in mechanical properties is primarily generated through the formulation of patterned shell and in-filled regions within the material during processing. This paper describes the formulation and results of a study to ascertain the impact strength of various full–infill polymer-based materials processed in various orientations and angles via fused deposition modeling. Ten different materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 51 publications
0
28
1
1
Order By: Relevance
“…The toughness plays a vital role in determining the energy absorbing capacity of a structure for high strain rate applications. Patterson et al (2019) investigated the impactabsorbing capacity of various materials printed at different build orientations (Table 1) and confirmed that the tougher material shows large plastic deformation before fracture. Caminero et al (2018) explained the procedure to 3D print continuous fibre composite specimens and also found the impact energy absorption by the composite (Figure 2).…”
Section: Introductionmentioning
confidence: 74%
“…The toughness plays a vital role in determining the energy absorbing capacity of a structure for high strain rate applications. Patterson et al (2019) investigated the impactabsorbing capacity of various materials printed at different build orientations (Table 1) and confirmed that the tougher material shows large plastic deformation before fracture. Caminero et al (2018) explained the procedure to 3D print continuous fibre composite specimens and also found the impact energy absorption by the composite (Figure 2).…”
Section: Introductionmentioning
confidence: 74%
“…At the end of the 2 weeks, the patient completed a short questionnaire about acceptance, safety, and satisfaction of the 3D printed brace, compared with the traditional brace produced by thermoforming. Moreover, thermographic images were obtained using an infrared thermal camera (One, Flir, USA) to objectively compare braces performances [18]. This study was performed in accordance with the Declaration of Helsinki, and the protocol was approved by the IRCCS E. Medea Ethics Committee.…”
Section: Pilot Patient Casementioning
confidence: 99%
“…Furthermore, impact tests are important to quantify the toughness of a material, by measuring the amount of energy absorbed during high-strain-rate conditions before failure. This behavior certainly changes with different production technologies, such as 3DP [18]. For these reasons, it is not yet possible to predict how the combination of virtual modeling and additive manufacturing processes affects the mechanical properties of a 3D printed brace.…”
Section: Introductionmentioning
confidence: 99%
“…FDM is the most suitable and least expensive method to produce scoliosis braces among these 3D printing techniques, despite having a bit less dimensional accuracy. A few studies have recommended the use of 3D printing to construct orthotic devices [ 83 , 84 , 85 ]. The majority of the researchers have fixated on the feasibility of developing devices with accurate geometrical dimensions and desired shapes, but quite a few studies have reported the cost and mechanical performances of these devices.…”
Section: Advancement In Spinal Rehabilitation Orthosesmentioning
confidence: 99%
“…Moreover, it is crucial to evaluate the toughness of the material through impact tests by measuring the energy absorbed for the duration of high strain rate conditions before failure. This behavior definitely varies with different production technologies, and the materials currently used for 3D printed orthotic devices do not provide the rigidity needed to correct the spine posture [ 85 ]. For these reasons, it is not yet possible to predict how the combination of virtual modeling and additive manufacturing processes affects the mechanical properties of a 3D-printed brace.…”
Section: Advancement In Spinal Rehabilitation Orthosesmentioning
confidence: 99%